Bahasa Melayu bahasa negara bangsa Malaysia - Che Rodi, Rozita; Musa, Hashim (Universiti Putra Malaysia Press, 2014)
Language is not merely a tool for communication and interaction. Language gives identity to a nation. Language also forms the spirit of the nation. Language plays a major role in shaping the identity and inculcates the esprit de corps, integration and dignity of a nation. In fact language use also reflects refines of character and the nobility of character and behavior of the people, which are the main basis for the formation of human civilization. Nonetheless, another main function of a language is also as a tool to record, accumulate, disseminate and pass down from one generation to another the treasure of knowledge and wisdom of the nation. An advanced society in respect of its civilization having elaborated systems of politics, government, economy, administration, law, defence, education, science, technology and communication, will naturally have an elaborated system of language and sophisticated literary and written tradition. Thus, language is the vehicle of a civilization, and a civilization is given the hue and pattern by its language use. All the contents and elements of a civilization will be understood by and encultured into the society by the particular language in use. The condition and status of thought and knowledge of a society are closely related to the condition of its language in use. Hence, the use of the Malay language, the indigenus language and national language of the people of Malaysia as the vessel and vehicle of knowledge, science, technology, education, writing and administration of the nation, will be able to develop the pattern, to form the shape, and to colour the development, achievement and advancement according to our local mould and character. This will develop our own inner strength and self-confidence to enable us to inculcate our own identity, dignity and pride of the nation into our society. This paper will analyse the issues of the Malaysian nationhood, the role of the Malay language as the vehicle for developing the Malaysian nation, and steps to be taken to empower the Malaysian society and nation in moving towards an advanced-nation status.